Effects of alkaline water intake on health: a systematic literature review - Mohd Zamli Tajudin, Maryam Hafizah; Hamirudin, Aliza Haslinda (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2020)
Introduction: The purpose of this study is to review the amount and duration of alkaline water intake and its impact towards human health outcomes. Methods: A systematic review was conducted and Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) was used. Elements of study questions which are population, intervention, comparison, outcomes and study design (PICOS) were used to determine the research objective. Inclusion and exclusion criteria were used to screen for relevant data. The articles were found through four electronic databases which were Scopus, Pro Quest, PubMed and Wiley Online Library. Specific terms were determined and searched by using Boolean Operators. Results: In total, 2370 relevant abstracts were identified, of which 11 full-text articles were evaluated with the following outcomes: positive (n=9), negative (n=1) and neutral (n=1). The amount and duration of alkaline water intake that produce positive effects is equivalent to standard fluid recommendation for various condition which were 2 L/day for general population, 4 L/day for athletes, 1 L/day for post-menopausal women and 2 L/day for diabetes mellitus patients. The duration of intervention to produce positive outcomes varied between one to four weeks. Conclusion: This systematic review provides the amount and duration of alkaline water intake that affect human health outcome. It is recommended for future study to explore the effects of pH and mineral contents of alkaline water because these two variables might produce different impact on the outcomes. Besides, it is suggested for meta-analysis to be conducted for more comprehensive clinical evidence.